CLINICAL-ANATOMICAL BASIS OF OPENING AND DRAINAGE OF PHLEGMON OF THE EYE AREA (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
This article explores the clinical-anatomical considerations underlying the opening and drainage of phlegmon in the eye area. Phlegmon, characterized by localized tissue inflammation and infection, poses significant challenges in ophthalmology. The study delves into the anatomical intricacies of the eye region, reviews relevant literature, presents methodologies for surgical intervention, reports results, engages in a comprehensive discussion, and concludes with suggestions for future research and clinical practice.